KERJASAMA SEKOLAH DAN KOMITE SEKOLAH DALAM MEMPERKUAT KARAKTERISTIK MURID MADRASAH TSANAWIYAH HIDAYATUL MUBTADI’IN LAMPUNG SELATAN - Saadah, Siti (Hijri, 2025)
This study aims to determine how the cooperation of schools and school committees strengthens the characteristics of students at MTs Hidayatul Mubtadi'in. This study uses a qualitative descriptive approach with primary and secondary data sources. In order to facilitate the data in this study, the author uses data collection techniques, namely observation, interviews, and documentation. The subjects of the study consisted of the Principal of MTs Hidayatul Mubtadi'in. The results of this study indicate that the School and the committee act as advisory agencies, supporting agencies and controlling agencies. The characteristics of students formed after the cooperation of the school and the committee in fulfilling the needs of teaching and learning activities in the form of facilities and infrastructure, namely: religious characteristics, honesty characteristics, tolerance characteristics and discipline characteristics.